A rare case of bilateral ocular manifestations of Sturge-Weber syndrome - Basyach, Pranami (International Journal of Research in Medical Sciences, 2021)
Sturge–Weber syndrome (SWS) is a group of phakomatoses characterized by hamartomas involving brain, skin and eyes. A 36 years old female presented with pain and diminution of vision in both eyes since last 1 year. On examination she has bluish sclera in B/L eyes with characteristic facial port-wine stain. Best corrected visual acuity (BCVA) in R/E- 6/18, N6 and in L/E- 6/6, N6. Intra-occular pressure (IOP) in R/E – 27 mm Hg and in L/E –18 mmHg. On gonioscopy – open angle B/E. On direct ophthalmoscopy and slit-lamp examination with 90 D lens, cup-disc ratio in R/E – 0.9 and in L/E – 0.7 with thinning of neuro-retinal rim in B/E. In optical coherence tomography (OCT), retinal nerve fibre layer (RNFL) and optic nerve head (ONH) it was confirmed. Other systemic examination – within normal limit. Initially, she had been on conservative treatment. As intraocular pressure remained high after several weeks of treatment, trabeculectomy in R/E done under local anaesthesia. No post-operative complications were seen. After 7 days of follow-up IOP – within normal limit, vision in R/E unchanged and had been frequently followed-up.